ANALISIS EFISIENSI BANK BUMD REGIONAL SUMATERA BERDASARKAN DATA ENVELOPMENT ANALYSIS (DEA) STUDI KASUS: BANK ACEH, BANK NAGARI DAN BANK SUMUT - Tri Agustina; Paidi Hidayat (Departemen Ekonomi Pembangunan USU, 2015)
Purpose of this study is to measure and to analyze the efficiency ratio of Bank Aceh, Bank Nagari, and Bank Sumut during 2011-2013. This study uses secondary data from financial statements that issued by each Bank and Bank Indonesia. Sampling technique in this research is purposive sampling with 3 regional enterprises from North Sumatera, Bank Aceh, Bank Nagari, and Bank Sumut. Measurement of efficiency in this study is using DEA method and intermediation approach. The input variables used in this study are deposits, assets, and labor costs, and output variables are total credit and income.The result of this study indicate that Bank Aceh and Bank Nagari has achieved an efficiency of 100% during 2011-2013. Bank Sumut efficiency is 100% in 2011 and 2013, in 2012 Bank Sumut efficiency achieuement 99.7%.Keywords: Efficiency, Bank Aceh, Bank Nagari, and Bank Sumut, Data Envelopment Analyze (DEA).